De l’inégalité parmi les chimpanzés : Sexe, drogues et individuation - David Jaclin (Revue de Primatologie)
Thousands of chimpanzees live in North America. No longer « wild » but not yet « domesticated », they inhabit a grey zone in our naturalistic tradition. In fact, their living conditions and the reactions that emerge from within these transformed environments provide unforeseen ethological material. Following certain of these pioneer existences, this article puts forward an original perspective on some animals’ situation in our current biopolitical economy and proposes substantial elements for an interdisciplinary inquiry. As a growing number of sanctuaries shelter animals rejected from biomedical industries, military experiments or Hollywood studios, a postnatural history of US chimpanzees suggests taking into account the diversity of situations where known living organisms experience unknown (re)organizations of life. Drawing on a multi-sited and multispecies ethnography, I present the story of Rachel, a veteran chimpanzee born in an Oklahoma breeding center. Once a millionaire couple’s pet, Rachel was sold to a laboratory by her nanny when the couple divorced. Leaving behind bubble baths and expensive wardrobes, she entered biomedical research and became a guinea pig for more than 10 years. She now lives in Quebec in a sanctuary that founder Gloria Grow describes as a curious mix of “a maximum security prison, a Zen retreat, an old folk’s home, and a Montreal Deli during the lunchtime rush”. By drawing biographical sketches of chimpanzees living in North American sanctuaries today, I focus on the mutagenic potential of humanimal interactions and question their communicational processes. Rather than examining what is or is not an Animal, I strive to reconsider what is a 21st century animal’s existence and shed a new light on adaptation processes as well as creative involutions, plasticity and (new) ways in which organisms express not only life, but vitality.